Interactive effects of silicon formulations, concentrations, and foliar application timing on rice physiology and yield - Velasco, Elena; Aranda, Xavier; Houben, Frank; Ribes, Juantxo; Araus, Jose L.; García-Caparros, Pedro (Frontiers in Plant Science, 2026)
The continuous increase in the cost of water and fertilizers associated with increasing global demand for food driven by population growth and the growing concern on the current environmental impact of agriculture led us to the urgent search for more sustainable agronomic practices. Among these, the use of biostimulants has emerged as a promising strategy to enhance crop productivity and resource-use efficiency while reducing reliance on conventional inputs. Nevertheless, identifying the most suitable type of biostimulant, along with the optimal method, dosage, and timing of application, remains particularly critical for staple crops such as rice, being an area that requires further in-depth research. In the present experiment, two silicon-based biostimulant formulations were tested under controlled conditions at two different concentrations and applied at different key phenological stages in rice through foliar spraying. Agronomical components (plant height, tiller number, aerial dry weight, grain yield, and harvest index), whole plant physiological parameters (vegetation indices such as NGRDI, TGI, GA and GGA readings), leaf traits (photosynthetic and transpirative gas exchange, total nitrogen and carbon concentration and the stable isotopic composition, pigment content), and the grains characteristics (mineral composition (macronutrients and heavy metal concentrations) were evaluated. Among the tested products, the Simosa formulation was the most effective, significantly enhancing tiller number, aerial dry weight, grain yield, chlorophyll concentration and nitrogen balance index. Nevertheless, no consistent dose-dependent effects were observed. In contrast, Siliforce-4 did not demonstrate clear effects on either biomass accumulation or physiological traits. Regarding rice grain consumption, only copper concentrations exceeded the threshold established by EFSA, 2009. Overall, these results underscore the need for further studies to determine the most effective silicon foliar fertilizer formulations, as well as optimal dose and timing of application for boosting rice productivity.